Efficient secretion of xylanase in Escherichia coli for production of prebiotic xylooligosaccharides. (1st June 2022) - Wang, Jiapeng; Zhang, Susu; Li, Chunhai; Liu, Xinli; Xu, Zhenshang; Wang, Ting
Abstract: The N-terminal 20 amino acid of Lactobacillus amylovorus feruloyl esterase (N20) was used as a signal peptide for fusion expression with a novel xylanase Xyl derived from Bacillus paralicheniformis . Results showed that N20-Xyl could be effectively secreted out of E. coli BL21(DE3) cells. Enzymatic characterization indicated that Xyl and N20-Xyl exhibited similar properties with the optimal pH of 8.0 and temperature of 50 °C. Furthermore, xylooligosaccharides were prepared through simultaneous xylanase secretion and xylan degradation by using E. coli . The final extracellular reducing sugar content reached 8.79 ± 0.10 g/L based on 40 g/L xylan, and the main products were xylobiose, xylotriose, and xylotetraose. Moreover, it was found that Levilactobacillus brevis 217-168, Enterococcus faecium 217-169, Pediococcus acidilactici 217-112, and Weissella confusa 217-162 could efficiently utilize these xylooligosaccharides for growth. Therefore, this study provided a method for the production of prebiotic xylooligosaccharides via simultaneous fermentation by using E. coli . Highlights: A novel xylanase Xyl derived from B. paralicheniformis was expressed in E. coli. The N20 of Lactobacillus amylovorus feruloyl esterase was used as signal peptide. Xylooligosaccharides were prepared via simultaneous N20-Xyl secretion and xylan degradation. The main products were xylobiose, xylotriose, and xylotetraose. The produced xylooligosaccharides could be used as prebiotic for LAB strains.